An Exquisite Mutual Authentication Scheme with Key Agreement Using Smart Card - Liao, C.-H.; Chen, H.-C.; Wang, C.-T. (Informatica)
An Exquisite Mutual Authentication Scheme with Key Agreement Using Smart Card